Kecemasan Penggunaan Bahasa Asing di Kelas AFL Dewasa : Penelitian - Amira Deani; Ghina’a Jayanthi Putri; Adib Alfalah; Andiana Perizga (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Anxiety is a feeling of fear, tension and apprehension about what’s to come. The purpose of this study was to determine the level of students' anxiety in foreign language learning and to find out the cause of anxiety that occurred in English classroom. The research methodology is descriptive quantitative study. Data collection techniques are questionnaire of foreign language class anxiety scale (FLCAS) adapted from Horwitz, E. K., Horwitz, M. B., & Cope, J. (1986) to determine the level of students' speaking anxiety and to find out the dominant type of anxiety that occurs. Furthermore, a structured interview in order to find the causes of the foreign language anxiety. The writer found that there are 2 students (10.5%) who experience